Editorial - International Journal of Sustainable Energy Planning and Management Vol 9 - Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2016)
This editorial introduces the ninth volume of the International Journal of Sustainable Energy Planning and Management. The volume addresses alternative ways of providing diesel fuel through emulsification ow waste cooking oil and fat, estimation of global solar energy potentials based on publically available data, and a large review of global grid connected electricity storage systems. Finally, an article applies stochastic programming to analyse optimal district heating expansion scenarios with particular focus on the phasing issue of investments in district heating grids.